Costly Persuasion - Gentzkow, Matthew; Kamenica, Emir (American Economic Review, 2014)
We study the design of informational environments in settings where generating information is costly. We assume that the cost of a signal is proportional to the expected reduction in uncertainty. We show that Kamenica & Gentzkow's (2011) concavification approach to characterizing optimal signals extends to these settings.